2001
DOI: 10.1034/j.1600-0706.2001.930305.x
|View full text |Cite
|
Sign up to set email alerts
|

Hatch or wait? A dilemma in reptilian incubation

Abstract: Animals often form groups to reduce the risk of predation through the per capita dilution of their individual predation risk. The advantages of grouping also influence the timing of reproduction in many species. In particular, synchrony in the timing of births may have evolved as a predator‐avoidance strategy as it dilutes the risk of predation upon vulnerable newborn and naive young. Eggs of an Australian freshwater turtle, Emydura macquarii, can hatch synchronously despite developmental asynchrony among eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 17 publications
3
105
2
2
Order By: Relevance
“…Embryo-embryo communication within a clutch is known in vertebrates, including birds and reptiles (Colbert et al 2010, Doody 2011, Spencer et al 2001, Vergne and Mathevon 2008, Vince 1966. In snakes, developing embryos use heart beats emanating from neighboring eggs as a clue for their metabolic level, to synchronize development and ultimately hatching (Aubret et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryo-embryo communication within a clutch is known in vertebrates, including birds and reptiles (Colbert et al 2010, Doody 2011, Spencer et al 2001, Vergne and Mathevon 2008, Vince 1966. In snakes, developing embryos use heart beats emanating from neighboring eggs as a clue for their metabolic level, to synchronize development and ultimately hatching (Aubret et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For embryo-embryo communication in vertebrates, cues such as sound production, egg vibration, increase in heart rates, odors, or carbon dioxide levels within the nest have been proposed as potential communication signals (Spencer et al 2001, Aubret et al 2016. In S. gregaria, synchronous hatching is observed when the eggs are incubated in a mass, but not when separated (Nishide and Tanaka 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Because all eggs within a clutch experience a similar incubation temperature, they hatch almost synchronously with their clutch mates, and at least some species are able to stimulate the hatching of clutch mates if the process has not already begun (Spencer et al, 2001). Synchronous hatching within a clutch results in incidental association among clutch mates and allows simultaneous digging activity of individual hatchlings.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases warm temperatures increase metabolic costs by an amount actually sufficient to retard growth (Porter and Tracy 1974). For example, O'Steen (1998) and Spencer et al (2001) found that cool-incubated turtles compensated by growing faster than warm-incubated turtles, and Rhen and Lang (1995) found that warm-incubated lizards grew more slowly. Letcher and Bengtson (1993) and Johnston et al (2001) report that fish given equivalent rations grow slower when maintained at warmer temperatures.…”
Section: Juvenile Stagesmentioning
confidence: 99%